The impact of interest rate risk on bank lending - Beutler, Toni; Bichsel, Robert; Bruhin, Adrian; Danton, Jayson (Journal of Banking & Finance, 2020)
This paper analyzes the transmission of realized interest rate risk to bank lending. It exploits unique supervisory information about the interest rate risk exposure of Swiss banks net of hedging. By weakening the banks’ economic capital, realized interest rate risk explains on average around one eighth or 30 basis points of the predicted total reduction in cumulative loan growth a year after an upward shock in nominal rates by one percentage point. Moreover, heterogeneity in exposures implies that the effects would differ across institutions. Finally, bank lending is mainly driven by the banks’ capital- rather than their liquidity-situation.